Visceral adipose tissue area and proportion provide distinct reflections of cardiometabolic outcomes in weight loss; pooled analysis of MRI-assessed CENTRAL and DIRECT PLUS dietary randomized controlled trials - Hadar Klein; Hila Zelicha; Anat Yaskolka Meir; Ehud Rinott; Gal Tsaban; Alon Kaplan; Yoash Chassidim; Yftach Gepner; Matthias Blüher; Uta Ceglarek; Berend Isermann; Michael Stumvoll; et al. (BMC Medicine)
Abstract Background Visceral adipose tissue (VAT) is well established as a pathogenic fat depot, whereas superficial subcutaneous adipose tissue (SAT) is associated with either an improved or neutral cardiovascular state. However, it is unclear to what extent VAT area (VATcm2) and its proportion of total abdominal adipose tissue (VAT%) are distinguished in predicting cardiometabolic status and clinical outcomes during weight loss. Methods We integrated magnetic resonance imaging (MRI) measurements of VAT, deep-SAT, and superficial-SAT from two 18-month lifestyle weight loss clinical trials, CENTRAL and DIRECT PLUS (n = 572). Results At baseline, the mean VATcm2 was 144.8cm2 and VAT% = 28.2%; over 18 months, participants lost 28cm2 VATcm2 (− 22.5%), and 1.3 VAT% units. Baseline VATcm2 and VAT% were similarly associated with metabolic syndrome, hypertension, and diabetes status, while VAT% better classified hypertriglyceridemia. Conversely, higher VATcm2 was associated with elevated high-sensitivity C-reactive protein (hsCRP), while VAT% was not. After 18 months of lifestyle intervention, both VATcm2 and VAT% loss were significantly associated with decreased triglycerides, HbA1c, ferritin, and liver enzymes, and increased HDL-c levels beyond weight loss (FDR < 0.05). Only VATcm2 loss was correlated with decreased HOMA-IR, chemerin, and leptin levels. Conclusions MRI follow-up of 572 participants over 18 months of weight loss intervention suggests that although increased VATcm2 and VAT% exhibit similar clinical manifestations, it might be preferable to examine VAT% when exploring lipid status, while VATcm2 may better reflect inflammatory and glycemic states. Trial registration CENTRAL (Clinical-trials-identifier: NCT01530724); DIRECT PLUS (Clinical-trials-identifier: NCT03020186).